Mapping the evolution of green finance for environmental sustainability through bibliometric analysis - Harshita Sharma; Swati Jain (Discover Sustainability)
Abstract Sustainability emphasises on protecting the environment, mitigating climate change, and encouraging social progress without having an adverse effect on Earth's life cycle or leaving anyone behind. Green financing is a key towards enhancing environmental sustainability and aligns with the Sustainable Development Goals, particularly SDG 7 (Affordable and Clean Energy) and SDG 13 (Climate Action). Everything that increases the flow of money to environmentally friendly initiatives is a part of green financing. Although there are a huge number of separate articles on green financing and environmental sustainability, but contribution of green financing towards environmental sustainability is still underexplored. The present study aims to conduct a bibliometric analysis to explore the recent trends in green financing and its contribution towards environmental sustainability. This paper analyses 5,750 research articles, extracted from SCOPUS database, related to green financing and environmental sustainability in various subject areas viz., energy, environmental science, and social sciences between 1996 and 2024. The most influential papers, authors, and sources were identified over a twenty-eight-year period through bibliometric and citation analysis. The present study focuses on the current trends in green financing and its contribution towards environmental sustainability. The study attempts to provide an extensive review of past literature and future research directions through bibliometric analysis using Biblioshiny by R and VosViewer.